Cancer immunotherapies: advances and bottlenecks - Rui, Rui; Zhou, Liqun; He, Shiming (Frontiers in Immunology, 2023)
Immunotherapy has ushered in a new era in cancer treatment, and cancer immunotherapy continues to be rejuvenated. The clinical goal of cancer immunotherapy is to prime host immune system to provide passive or active immunity against malignant tumors. Tumor infiltrating leukocytes (TILs) play an immunomodulatory role in tumor microenvironment (TME) which is closely related to immune escape of tumor cells, thus influence tumor progress. Several cancer immunotherapies, include immune checkpoint inhibitors (ICIs), cancer vaccine, adoptive cell transfer (ACT), have shown great efficacy and promise. In this review, we will summarize the recent research advances in tumor immunotherapy, including the molecular mechanisms and clinical effects as well as limitations of immunotherapy.